Forestry in Natural Resources Development and Management - Das, D.C. (Journal of Soil and Water Conservation, 2022)
In last five years them had been a steady loss of perception of the durable and long terns effects of Watershed management for bringing in an inter- dependent land management system. This is particularly discerntrable in programmes on the improved, acceptable and sustainable productivity of rainfed agriculture, moderation of and sedimentation and deferent to water stress and drought conditions. To achieve short term gains in productivity, the need of durable assets like perennial vegetation and network of a land treatment system for improvement of moisture regimes through conservation, recharge and reuse, are being discounted. The overall socio-economic are not being worked out rationally. Low cost is being taken as cost effectiveness. This has been happening, surprisingly inspite of the rich scientific and traditional evidence obtained within the country over last 40 years and which have been made available to the developing countries by the Indian experts through world bodies and bilaterally.It has, therefore, become necessary to bring forth together some of these results and experiences specially those concern forestry rather perennial vegetation and to put across to the soil and water conservationists who are working all over the country. The paper has been prepared to achieve this goal